Effectiveness of the Implementation of Stunting Prevention Policies in Bakti Jaya Village (Wiyatamandala, 2025)
Stunting is often a serious public health problem because it can negatively impact children's physical and cognitive development. Children who are stunted tend to have a higher risk of developing diseases, poor school performance, and difficulty in reaching their full potential physically and intellectually. This condition can be the result of poor diet, nutritional deficiencies, frequent infections, and other environmental factors. This study aims to see the extent of stunting prevention policies in Bakti Jaya Village. The research method used is qualitative research with narrative descriptiveness. With the results of the study showing that the implementation of stunting prevention policies in Bakti Jaya village has been running effectively in accordance with applicable policies, it can be seen through the reduction of stunting prevalence from 2022-2024.